2015
DOI: 10.17159/0379-4350/2015/v68a26
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic insight into the activation of n-octane with alkaline-earth metal hydroxyapatites

Abstract: Alkaline-earth metal hydroxyapatites are prepared by the co-precipitation method and characterized using XRD, ICP, NH 3 -TPD, SEM-EDX, TEM and N 2 physisorption analysis. The metal present in the hydroxyapatite influences the acidity of the catalyst. Oxidative dehydrogenation reactions carried out in a continuous flow fixed bed reactor showed that the selectivity towards desired products was dependent on the alkaline-earth metal in the hydroxyapatite. All hydroxyapatite catalysts showed high selectivity toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A variety of classes of catalysts have been employed for the ODH of n-octane. These include unsupported metal oxides [43][44][45][46], supported metal oxides [47][48][49][50][51][52], mixed metal oxides, zeolites [53,54] and hydroxyapatites [24,[55][56][57]. This review focuses on unsupported and supported metal oxides.…”
Section: Catalysts Usedmentioning
confidence: 99%
See 4 more Smart Citations
“…A variety of classes of catalysts have been employed for the ODH of n-octane. These include unsupported metal oxides [43][44][45][46], supported metal oxides [47][48][49][50][51][52], mixed metal oxides, zeolites [53,54] and hydroxyapatites [24,[55][56][57]. This review focuses on unsupported and supported metal oxides.…”
Section: Catalysts Usedmentioning
confidence: 99%
“…The combined acidity of the phosphate groups and the alkali earth metal create active sites which are capable of activating oxygen, resulting in oxygen species that are able to abstract hydrogen in alkanes [64]. Dasireddy et al [56] reported the use of alkali earth metal hydroxyapatites in the oxidation of n-octane. The conversion increased with an increase in temperature, which was reported to be due to the surface oxygen species chemisorbed on the catalyst (Figure 10).…”
Section: Unsupported Metal Oxidesmentioning
confidence: 99%
See 3 more Smart Citations